Resíduo úmido cervejeiro como substrato para obtenção de extrato enzimático amilásico por Aspergillus niger NCQS 40371 - Santana, Fátima Rodrigues (2021)
The lignocellulosic residues of agro-industrial origin are found in great abundance, with low added value and easy to obtain. As a result of its properties, its use proves to be very promising for obtaining enzymes such as amylase, through techniques such as solid state fermentation (SSF). Microbial enzymes are of great biotechnological importance and applicable in various sectors of industry. Based on this principle, the aim of the present study was to obtain the crude amylasic extract through SSF using the WBG as substrate through the fungus A. niger NCQS 40371. Initially, the physical-chemical characterization of the WBG was carried out, followed by the determination of the best particle size for fermentation (16 mesh Tyler and without particle size separation). For the optimization of the SSF a complete factorial design 33 was used, evaluating the pH, temperature (°C) and humidity (%). From the best superior result, the enzymatic production kinetics and its partial characterization were obtained, through the determination of the optimum pH, thermostability, in addition to the effect of time and added in the enzymatic extraction. The results of the characterization of WBG, which is the same rich in carbohydrates and proteins. The SSF in 16 mesh Tyler showed the best enzymatic production (48.56 U / g), being used for the other assays. The experimental design showed that the variables studied are for the process, with the best enzymatic activity (215.26 U / g) being obtained at pH 5, 32 °C and 70% humidity. The enzymatic obtainment kinetics demonstrate that a maximum production occurs in 96 h of fermentation. As for partial enzymatic characterization, the best pH is found at 4.5 and thermostability is reached at 50 °C, maintaining a relative activity at 80% after 48 h. The extraction time and beverage dissipate independently, obtaining the best enzymatic extraction in 60 minutes at 100 rpm. With the results obtained, it can be concluded that the WBG presents itself as a promising substrate to obtain the amylase enzyme.